The determination of the conduction mechanism and extraction of diode parameters of ITO/PEDOT-PSS/POLYMER/Al heterojunction diode - Sahingoz, Recep; Soykan, Cengiz; Yakuphanoğlu, Fahrettin; Voigt, Monica; Cetin, Hidayet (Elsevier Science Bv, 2006)
ITO/PEDOT-PSS/POLYMER/Al heterojunction diode was fabricated. The current-voltage characteristics have been studied to explain of rectification generation and the luminance-voltage (L-P) characteristics of the diode have also been investigated. The diode shows non-ideal I-V behavior with an ideality factor greater than unity. The conduction mechanism was determined and a Schottky type conduction process was defined. The diode parameters such as barrier height and ideality factor were found as 0.71 eV and 2.07, respectively. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: heterojunction diode; luminance; poly[2-(2-naphtylamino)-2-oxo-ethyl methacrylate]